Global Comprehensive Outlook of Hantavirus Contagion on Humans: A Review - Ashique, Sumel; Sandhu, Navjot K; Das, Supratim; Haque, Sk. N.; Koley, Kartick (Infectious Disorders - Drug Targets, 2022)
Hantaviruses are rodent viruses that have been identified as etiologic agents of 2 diseases in humans: Hemorrhagic Fever with Renal Syndrome (HFRS) and Nephropathiaepidemica (NE) in the Old World and Hantavirus Pulmonary Syndrome (HPS) in the New World. Orthohantavirus is a genus of single-stranded, enveloped, negative-sense RNA viruses in the family Hantaviridae of the order Bunyavirales. The important reservoir of Hantaviruses is rodents. Each virus serotype has its unique rodent host species and is transmitted to human beings with the aid of aerosolized virus, which is shed in urine, faeces and saliva and hardly by a bite of the contaminated host. Andes virus is the only Hantavirus identified to be transmitted from human-to-human and its major signs and symptoms include fever, headache, muscle aches, lungs filled with fluid, etc. In early 1993, this viral syndrome appeared in the Four Corner location in the southwestern United States. The only accepted therapeutics for this virus is Ribavirin. Recently, serological examinations to identify Hantavirus antibodies have become most popular for investigation among humans and rodent reservoirs.
Keywords: transmission